수산기로 치환된 벤조페논 그룹의 자외선 차단 소프트 콘택트렌즈로의 응용 - 김득현; 성아영 (대한시과학회지, 17(1), 2015)
목 적: 본 연구는 hydroxybenzophenone계 물질을 첨가제로 소량의 비율로 사용하여 소프트 콘택트렌즈 제조 후 광학성 및 물리적 특성을 분석하여 콘택트렌즈 재료로서 활용도를 알아보았다. 방법: 소프트콘택트렌즈의 주재료인 HEMA와 개시제인 AIBN을 기본조합으로 하고 2-hydroxy- benzophenone, 2,4-dihydroxybenzophenone 그리고 2,4,4-trihydroxybenzophenone을 첨가제로 사용하여 각각 공중합하였다. 결과: 2-Hydroxybenzophenone을 첨가한 콘택트렌즈의 경우 UV-A 86.8~72.2%, UV-B 84.2~70.4%로 소량의 자외선 차단 효과를 나타내었다. 또한 2,4-dihydroxybenzophenone 경우 UV-A 76.2~16.8%, UV-B 66.8~2.0%로 2,4,4,-trihydroxybenzophenone의 경우 UV-A 61.8~11.6% UV-B 50.8~1.4%로 두 물질 모두 자외선 차단 효과가 다소 있는 것으로 나타났다. 결론: 본 실험 결과로 볼 때 소량 첨가하였을 때 2,4-dihydroxybenzophenone 및 2,4,4,- trihydroxybenzophenone의 경우 자외선 차단 기능을 가진 콘택트렌즈로 다양하게 사용될 것으로 판단된다. Purpose: The optical and physical characteristics of soft contact lens ploymerized with hydroxybenzophenone group in the basic soft contact lens material were evaluated. Methods: 2-Hydroxybenzophenone, 2,4-dihydroxybenzophenone and 2,4,4-trihydroxybenzo- phenone were used as additives and also, the mixture containing 2-hydroxyethyl methacrylate and additive copolymerized in the presence of AIBN as an initiator. Results: The optical properties of produced contact lens including 2-hydroxybenzophenone showed that the UV-A transmittance was 86.8~72.2%, the UV-B transmittance was 84.2~70.4%, Also, in case of contact lens including 2,4-dihydroxybenzophenone and 2,4,4-trihydroxybenzophenone, the results showed that the UV-A transmittance were 76.20~16.80%, 61.80~11.60%, and the UV-B transmittance were 66.80~2.00%, 50.80~1.40%, respectively. The addition of 2,4-dihydroxy- benzophenone and 2,4,4-triyhydroxybenzophenone allowed the contact lense to block UV. Conclusions: Based on the results of this study, the hydroxybenzophenone group is suitable for use as a material to UV-blocking high performance contact lenses. KCI Citation Count: 5